Fluctuation in Foreign Exchange Rates and Profits in Commercial Banks Case Study of Stanbic Bank Mukono Branch - Kisaakye Esther Ssembiro (Uganda Christian University, 2024)
Financial performance is determined by the capability to support operational and investment choices as well as plans to reach financial stability in a business. It signifies the degree to which a bank has met its financial goals based on predetermined financial targets and standards. Changes in the exchange rate influence the domestic prices through three channels, via imported consumption goods' prices, imported intermediate goods' costs, and domestic goods priced in foreign currency. Risks from fluctuations in foreign exchange rates The risk of change in foreign exchange rates is deemed as one of the biggest risks to banking organizations. Worst case, high foreign exchange losses might even lead to the failure of banks. The aim of the research was to determine the effects of exchange rate changes on the financial results of commercial banks in Uganda. The research employed a descriptive research design, which was suitable because the goal was to develop a profile on how exchange rate fluctuations impact the financial performance of commercial banks in Uganda. All commercial banks operating in Uganda were included in the target population. The information was sourced from the bank's consolidated financial statements from a secondary source. SPSS, Statistical Package for Social Scientists, was utilized in the data analysis for the study. The research confirmed a positive link between changes in foreign exchange rates and banks' financial performance, assessed by the assets' returns ratio. It was also determined that the correlation between the fluctuations and the returns was not very strong. Results from the analysis of correlation established that a fluctuation in the value of a home currency lead to an effect on the financial performance of the bank. The study concluded that there was a weak relationship between foreign exchange rate fluctuations and the performance of commercial banks in Uganda. The study recommended that relevant authorities-for instance, the central bank of Uganda-should adequately put in measures to safeguard the value of the domestic currency. This would ensure that the value of the same does not fluctuate much day in and day out.